1984
DOI: 10.1056/nejm198405313102204
|View full text |Cite
|
Sign up to set email alerts
|

Des-γ-Carboxy (Abnormal) Prothrombin as a Serum Marker of Primary Hepatocellular Carcinoma

Abstract: We detected des-gamma-carboxy prothrombin, an abnormal prothrombin, in the serum of 69 of 76 patients (91 per cent) with biopsy-confirmed hepatocellular carcinoma (the mean level of the abnormal prothrombin was 900 ng per milliliter). In contrast, levels of the abnormal prothrombin were low in patients with chronic active hepatitis (mean, 10 ng per milliliter) or metastatic carcinoma involving the liver (mean, 42 ng per milliliter), and undetectable in normal subjects. In five patients treated with vitamin K t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
300
1
6

Year Published

1995
1995
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 559 publications
(312 citation statements)
references
References 23 publications
5
300
1
6
Order By: Relevance
“…DCP, also known as prothrombin induced by vitamin K absence-II (PIVKA-II), is an abnormal prothrombin protein that is present at higher levels in the serum of HCC patients. Since the report by Liebman et al [18], DCP has been recognized as not only a highly specific marker for HCC but also a predictor of prognosis of HCC patients [86,87]. AFP-L3 is a fucosylated variant of AFP that reacts with Lens culinaris agglutinin A and can differentiate an increase of AFP due to HCC from that due to benign liver disease [20,21,82].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…DCP, also known as prothrombin induced by vitamin K absence-II (PIVKA-II), is an abnormal prothrombin protein that is present at higher levels in the serum of HCC patients. Since the report by Liebman et al [18], DCP has been recognized as not only a highly specific marker for HCC but also a predictor of prognosis of HCC patients [86,87]. AFP-L3 is a fucosylated variant of AFP that reacts with Lens culinaris agglutinin A and can differentiate an increase of AFP due to HCC from that due to benign liver disease [20,21,82].…”
Section: Discussionmentioning
confidence: 99%
“…To date, many tumor markers have been proposed as a complement or substitute for AFP in the diagnosis of HCC, such as des-gamma-carboxyprothrombin (DCP) [18,19], Lens culinaris agglutinin-reactive fraction of AFP (AFP-L3) [20,21], and various cytokines [22][23][24]. The aim of this study is to compare the diagnostic accuracy of AFP in small HCC with other biomarkers and to find the optimal cutoff value of each tumor marker for efficient surveillance.…”
Section: Introductionmentioning
confidence: 99%
“…Since the report by Liebman et al [171], DCP has been recognized as not only a highly specific marker for HCC but also a predictor of prognosis of HCC patients [172,173]. According to the systematic review, the sensitivity, specificity, and LR?…”
Section: Des-c-carboxyprothrombinmentioning
confidence: 99%
“…The best known is alpha-fetoprotein, which we have found to be elevated in about 50% of our HCC patients (Virji et al, 1992). By contrast, the more recently recognized marker DCP (des-γ carboxy prothrombin) has been found to be increased in over 70% of patients with HCC, although it is less specific than AFP, since it is also increased in biliary diseases and by the anticoagulant action of warfarin (Weitz et al, 1993;Huisse et al, 1994;Liebman et al, 1984;Nakao et al, 1991;Liebman et al, 1989;Li et al, 2002,Lefrere et al, 1987,Shah et al, 1987Tsai et al, 1990). The action of warfarin has been identified to be on the vitamin K cycle, in which oxidized vitamin K cannot be cycled back to the reduced and physiologically active form (Fasco et al, 1982), when warfarin was present.…”
Section: Discussionmentioning
confidence: 98%
“…As a result, the underlying normal liver produces mature prothrombin, but HCCs within that liver produce under-carboxylated or immature prothrombin, DCP, one of the more useful HCC serum markers (Weitz et al, 1993;Huisse et al, 1994;Liebman et al, 1984;Nakao et al, 1991;Liebman et al, 1989;Li et al, 2002). The biological significance of this has never been clear, but it has recently been suggested that immature prothrombin or DCP has HCC growth promoting properties (Suzuki et al, 2005).…”
Section: Introductionmentioning
confidence: 99%